372 Effects of probiotic Enterococcus faecium in shelter cats. (7th December 2018) - Gordon, R; Denny, M; Williams, L; Spangler, D; Kitts-Morgan, S
Abstract: Cats surrendered to shelters come from diverse situations, and many may not have received adequate diets or general health care prior to arrival at a shelter. These inadequacies along with environmental stress may contribute to loose stool often observed in shelter cats. Few studies have investigated the effects of probiotics in shelter cats. Therefore, the objective of this study was to determine effects of probiotic supplementation on DMI, BW, body condition scores, and fecal scores of shelter cats. Thirty adult cats (17 male, 13 female) with BW of 3.05 ± 0.08 kg were obtained from a local shelter and used in a 28 d crossover study. Following adaptation for 10–14 d, all cats received Purina Pro Plan® Focus Adult dry cat food for 14 d (control period), followed by dry food + once daily FortiFlora™ probiotic (1 x 10 8 CFU/g Enterococcus faecium ) for 14 d (probiotic period). Body condition scores (1–9 scale) and BW were measured weekly, and fecal scores (1–7 scale; 1=hard, 7=watery) were recorded daily. Dry matter intake decreased (P=0.001) by 2.3% during the probiotic compared to control period. Over the course of the experiment, BW increased (P < 0.0005) by 7.7%, and body condition score tended (P=0.06) to increase for probiotic (4.84 ± 0.082) compared to control (4.75 ± 0.085) period. Fecal score increased (2.83 ± 0.121; P=0.005) during week 1 of probiotic supplementation compared to week 2 of the control period (2.45 ± 0.091). While increased fecal score indicated decreased fecal quality, it remained within an acceptable range of fecal quality. By week 2 of probiotic supplementation, fecal scores decreased (P=0.02) and were similar to control period fecal scores. These results suggest a negligible benefit of two-week probiotic supplementation to shelter cats compared to feeding quality dry food alone.